THE EFFECTIVENESS OF CHITOSAN TOXICITY TO CONTROL THERMITES (Coptotermes curvignathus HOLMGREN) AT RUBBER PLANT - Zaida Fairuzah; Aidi Daslin (Pusbindiklat - LIPI, 2011)
Thermite (Coptotermes curvignathus) is the destructive pest at rubber plantation especially rubber planta-tion which is ex of old plantation or forest with inaccurate land clearing. Chitosan known can control thermites by disturbing protozoa’s rules in digestion systems of thermites that causing thermites can not get the food yielded by protozoa. Effectiveness of Chitosan was known by directly testing chitosan to thermites with the pre eliminary test to get the range of effective concentration and way of effective application with 8 treatments in 4 concentration levels ( 0.1, 1, 10, and 100%) which is each concentration combined with two way of application (spraying and baiting) with 4 replications. Based to the result of pre eliminary test, 1% chitosan concentration determined as concentration standard of main test which consists of concentration test (0.1, 0.5, 1, and 2%) with the spraying application with 4 replications with control and termicide as comparitors. The same concentrations and compari-tors were also tested with the baiting application with 4 replications. Then, the test also done by combinating spraying and baiting application with same concentrations (0.1, 0.5, 1, and 2%) and compared with control and termiticides that replicated 3 times. The percentage of thermites mortality was observed every two days until the 4th day after application. The result showed that the combination treatment between concentration and way of application of chitosan showed that the most effective concentration to kill the thermites is 2% baiting application with the mortality percentage of thermites reaches 54.78% at the 4th day after application